Correlation Between Sleep Quality and Acne Vulgaris Incidents Among Medical Students in Surabaya - Parmasari, Wahyuni Dyah; Siswanto, Tansatrisna Vony Rei; Suhartati, Suhartati (Faculty of Medicine Universitas Sebelas Maret, 2025)
Introduction: The symptoms of acne vulgaris, a chronic inflammatory condition of the sebaceous glands, include comedones, papules, pustules, and nodules. Eighty to one hundred percent of people have acne vulgaris. Adolescent boys aged 16-19 and females aged 14-17 had the highest incidence. It is projected that sleeping late at night would enhance the activity of androgenic hormones, which regulate the mechanism of sebum production in the skin. This will make the skin greasier, making it more prone to acne than normal, dry skin. Reviewing the association between acne vulgaris incidence and sleep quality among 17-23-year-old students at Wijaya Kusuma University’s Faculty of Medicine in Surabaya was the aim of the Study.Methods: Data from 196 respondents were gathered for this study using a cross-sectional survey method. All sample is a females. When analyzing data, SPSS Statistics is used to process the Chi-Square Test.Results: The study’s findings indicate that 83 respondents (58,5%) had mild acne vulgaris, 52 respondents (36,6%) had moderate acne vulgaris, and 7 respondents (4,9%) had severe acne vulgaris. Of the respondents, the majority (116 respondents, 81,7%) did not have enough sleep or had poor quality of sleep. While 26 respondents (18,3%) had a good quality of sleep. The Chi-Square test findings indicated a correlation between the incidence of acne vulgaris and sleep quality, with a value of 0.04<0.05.Conclusion: The strain of studying and a full lecture schedule can make it difficult to manage their time effectively, leading to a lack of sleep patterns and quality. Hormones are impacted, and a contributing element is an unclean face.